KEPUASAN MASYARAKAT DALAM PENINGKATAN KESEJAHTERAAN TERHADAP SERAPAN DANA DESA DI DESA MOODULIO KECAMATAN BONE KABUPATEN BONE BOLANGO - Bempa, Indrawati; Imran, Harijono; Mohi, Widya Kurniati (Program Studi Akuntansi, 2020)
The purpose of this research is to determine community satisfaction with the absorption of village funds in Moodulio Village, Bone District, Bone Bolango Regency. This study uses a qualitative research approach, using data sources through interviews and documentation studies. The results of the study concluded that the Village Fund Allocation (ADD) sourced from the central and regional government financial balance funds greatly affected the rate of development of each village. Likewise with Moodulio Village, Bone District, Bone Bolango Regency, with the current ADD, Moodulio Village is very helpful in carrying out village development in stages for the realization of community welfare